Avaliação no Processo Ensino-Aprendizagem: uma Experiência Vivenciada - Ferreira, Maria De Lourdes Da Silva Marques [UNESP] (Associação Brasileira de Educação Médica, 2021)
Evaluation (grading) is crucial for the teaching and learning process since it provides data on the process and allows one to review course objectives, methodology, and content. Considering evolutions as a permanent process of self-education, this study aimed to evaluate how students perceive its role in the difficulties encountered during the daily educacional process. The data collection instrument was a questionnaire that was filled out daily by students. The majority of the students classified the audiovisual resources, clarity of exposure of the course content, development of the class itself and comprehension of the content as excellent. They saw both themselves and the professor-facilitator as motivated in the teaching-learning process, based on objectivity and critical discussion. As for their overall analysis, the following categories merged; duration of the theoretical section, which they considered too short; professor-student relationship as a learning incentive; innovative teaching-learning strategies; adequate communication, and importance of daily grading. They felt that objectives and criteria for grading on theoretical content allowed students to evaluate their own progress thus making it possible to adjust the teaching to their needs and enabling professors to evaluate the effectiveness of their own performance.

A avaliação é fundamental no processo ensino-aprendizagem, pois fornece dados desse processo e permite prever objetivos, metodologia e conteúdo. Considerando a avaliação como um processo permanente da auto educação, este estudo objetivou avaliar como os alunos percebem sua participação no desenvolvimento do conteúdo teórico ministrado na área de ginecologia e identificar as dificuldades encontradas durante o processo educativo diário. O instrumento de coleta de dados foi um questionário aplicado diariamente. A maioria dos alunos classificou os recursos audiovisuais, clareza da exposição e desenvolvimento da aula, bem como a compreensão do conteúdo como ótimos. Consideraram-se motivados, e o professor-facilitador da aprendizagem pela objetividade e discussão crítica. Quanto à análise, as categorias emergidas foram duração do bloco teórico, considerada pequeno relacionamento professor aluno como fator de incentivo à aprendizagem; estratégica de ensino aprendizagem inovadora, comunicação adequada e avaliação diária importante. Considerou-se que os objetivos e os critérios da avaliação teórica permitiram aos alunos avaliar seu progresso, possibilitando adequar o ensino às suas necessidades, e o professor pode avaliar a efetividade de seu desempenho.
An Experience with Evaluation in the Teaching and Learning Process
Keywords: Education Nursing; Evolution; Teaching; Learning; Educação em Enfermagem; Avaliação; Ensino; Aprendizagem